2021
DOI: 10.1101/2021.06.07.21258332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-dose mRNA vaccine effectiveness against SARS-CoV-2, including P.1 and B.1.1.7 variants: a test-negative design in adults 70 years and older in British Columbia, Canada

Abstract: Introduction: Randomized-controlled trials of mRNA vaccine protection against SARS-CoV-2 included relatively few elderly participants. We assess singe-dose mRNA vaccine effectiveness (VE) in adults ≥70-years-old in British Columbia (BC), Canada where the second dose was deferred by up to 16 weeks and where a spring 2021 wave uniquely included co-dominant circulation of B.1.1.7 and P.1 variants of concern (VOC). Methods: Analyses included community-dwelling adults ≥70-years-old with specimen collection between… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The results of the quality assessment of all the included studies are shown in Supplementary Table S2. Before 1 July 2021, 24 of 39 studies were published in peer-reviewed journals [9,12,[15][16][17]19,22,24,25,[28][29][30][31]33,34,36,37,[40][41][42]45,47,48,50] while the remaining 15 studies were posted online as preprint articles [11,18,20,21,23,26,27,32,35,38,39,43,44,46,49]. The characteristics of the studies are shown in Supplementary Table S1, including the country, study design, types of vaccines, outcomes, and SARS-CoV-2 variants involved in the studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the quality assessment of all the included studies are shown in Supplementary Table S2. Before 1 July 2021, 24 of 39 studies were published in peer-reviewed journals [9,12,[15][16][17]19,22,24,25,[28][29][30][31]33,34,36,37,[40][41][42]45,47,48,50] while the remaining 15 studies were posted online as preprint articles [11,18,20,21,23,26,27,32,35,38,39,43,44,46,49]. The characteristics of the studies are shown in Supplementary Table S1, including the country, study design, types of vaccines, outcomes, and SARS-CoV-2 variants involved in the studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The outcomes include all laboratory-confirmed SARS-CoV-2 infection, asymptomatic and symptomatic infection, hospitalization, critical disease, and death. As for evaluating the protective effects of the vaccine on SARS-CoV-2 variants, 5 studies mentioned the approximate prevalence of variants in the region of the study population [18,19,28,34,49], and 11 studies calculated the number or percentage of cases with variants among all or sampled participants with a positive test of SARS-CoV-2 variants [20,26,31,33,[36][37][38]42,43,46,48]. Only three studies evaluated the VE against specific VOC, in which one study from Qatar reported the VE against B.1.1.7 and B.1.351 [9], one study from Canada studied VE against B.1.1.7 and P.1 [46], and the other one study from the UK evaluated the VE against B.1.1.7 and B.1.617.2 (delta variant) [20].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations